Forbidden fruit, and other stories - La Rosa, Pablo (Arte Público Press, 2017)
"In masterful tales of coming of age and becoming marginalized during the Cuban Revolution and its aftermath, Pablo La Rosa nostalgically looks back at a childhood spent by the seaside and creates a mosaic of poignant experiences seen through the glaring lenses of race and exile. Neither the advantages of race or education, however, can exempt the disoriented protagonists from their perceived loss of homeland, integrity, identity. In the masterful "El Marielito," he captures the bewilderment of a black man, marginalized by his race and circumstances in pre and post revolutionary Cuba and during his exile in the United States. Equally on the margin in spite of the advantages of education and race, a Cuban college student can relate only to a Russian janitor; though they share no common language they wordlessly share a longing for their lost homelands."